2016
DOI: 10.1002/chem.201505019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Influence of Side‐Chain Conformation on Glycosylation Selectivity using Conformationally Restricted Donors

Abstract: The synthesis of a series of conformationally locked mannopyranosyl thioglycosides in which the C6-O6 bond adopts either the gauche,gauche, gauche,trans, or trans,gauche conformation is described, and their influence on glycosylation stereoselectivity investigated. Two 4,6-O-benzylidene protected mannosyl thioglycosides carrying axial or equatorial methyl groups at the 6-position were also synthesized and the selectivity of their glycosylation reactions studied to enable a distinction to be made between steric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 72 publications
(63 reference statements)
1
34
0
Order By: Relevance
“…7376 Glycosyl donors on which the gt -conformation has been imposed are less reactive 82,83 and less prone to the formation of axial glycosides than their gg -isomers. 33,84 Therefore, the comparable selectivity of 13 and 27 appears to arise from the fortuitous cancelling of the effect of the axial azide group in 13 by the switch to the predominant gt –conformation of its side chain. Extrapolating to the L-glycero-L-manno configuration found in the pseudaminic acid itself, the hypothetical donor 52 can be expected to populate the tg -conformation (Figure 4), which is the most electron-withdrawing and which leads to the expectation of high equatorial selectivity in glycosylation reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7376 Glycosyl donors on which the gt -conformation has been imposed are less reactive 82,83 and less prone to the formation of axial glycosides than their gg -isomers. 33,84 Therefore, the comparable selectivity of 13 and 27 appears to arise from the fortuitous cancelling of the effect of the axial azide group in 13 by the switch to the predominant gt –conformation of its side chain. Extrapolating to the L-glycero-L-manno configuration found in the pseudaminic acid itself, the hypothetical donor 52 can be expected to populate the tg -conformation (Figure 4), which is the most electron-withdrawing and which leads to the expectation of high equatorial selectivity in glycosylation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have previously demonstrated that even the simple inversion of configuration at the 7-position in NeuAc affects the reactivity and selectivity of the widely used O4,N5-oxazolidinone-type sialyl donors, 32 due to the imposed change in side chain conformation. 33 Moreover, the influence of the N5 protecting group on the stereoselectivity in the formation of NeuAc glycosides is widely reported, 3440 and the replacement of an equatorial substituent (typically a C-O bond) by the axial equivalent typically influences reactivity and selectivity of glycopyranosyl donors. 41–50 …”
Section: Introductionmentioning
confidence: 99%
“…This conformation orientates the C6–O bond approximately parallel to the pseudoaxial substituents, favoring an axial attack from the nucleophile ( Scheme 84 ). Reactions with glucal substrates 295 gave products with higher stereocontrol than rhamnals 296 , which was attributed to the conformational preference of the C6 side-chain, 340 which is lacking in the rhamnal moieties. This report further highlights the importance of considering the effect that protecting groups have on the conformation of putative reaction intermediates and how these can be used to achieve stereocontrol.…”
Section: Organocatalysis Applied To Deoxyglycoside Synthesismentioning
confidence: 99%
“…Low temperature NMR analysis of the reaction mixture following pre‐activation indicated the α‐glycosyl triflate was the major resting intermediate . This was attributed to the cyclic benzylidene group locking the C5–C6 bond in trans ‐ gauche conformation . Consequently, the C6–O6 bond is kept antiperiplanar to C5–O5 bond, maximizing its electron‐withdrawing effect and destabilizing the electron deficient 9 , .…”
Section: The Effect Of 46‐o‐benzylidene Acetal On Stereoselectivitymentioning
confidence: 99%